Designing Interactive Workbook via Liveworksheets for Reading Skill at Grade 10 - Cellia Apridita Cahya Utami; Dewi Nopita; Gatot Subroto (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This research aimed to design interactive workbook via Liveworksheets for reading skill at tenth grade. The subject of this research was a class of 10th grade students in a Senior High School in Tanjungpinang, which consisted of 16 students. This research was research and development with the ADDE model based on Richey and Klein (2014). This research focused on designing interactive workbook for the tenth grade second semester English materials. It consisted of announcement text, recount text, and narrative text. There were four phases in this research which are analysis phase, design phase, development phase, and evaluation phase. The result from the validation stage showed that there was minor revision in the media aspect. After the revision had been approved by the validator, the interactive workbook was decent to be used in the classroom. From the practical result, it can be seen that the interactive workbook got good responses from the students. The interactive workbook also met the students’ characteristics which were classified as generation Z.